Crossed Aphasia. I: A Case-Study with Purely Deep Lesion - M. Laiacona; C. Stangalino; L. Lorenzi (Behavioural Neurology)
In this paper, we describe the case of a right-handed man, MR, who after right thalamic haemorrhage presented subtranscortical aphasia. Of the disturbances generally associated with standard left hemisphere functions, the patient presented acalculia but not apraxia. Among the functions attributed to the standard right hemisphere, MR showed impairment in affective language and presented unilateral neglect and a strong position preference.